Odpowiedzi

2009-11-07T11:55:56+01:00
(4√3-7)²=48-2*4√3-*7+49=48-56√3+49=97-56√3


(2+3√5)×(3-2√5)=6-4√5+9√5-30=5√5-24
2009-11-07T12:00:11+01:00
(4√3-7)²=(4/1*1/3-7)2=(4/3-7)2=(5 2/3)2=5 2/3* 5 2/3=17/3*17/3=289/9=32 i 1/3

(2+3√5)×(3-2√5)=2 3/5*2 3/5=13/5*13/5=169/25=6 19/25
Najlepsza Odpowiedź!
2009-11-07T12:17:19+01:00
Do tego potrzebny jest wzór skróconego mnożenia (a-b)²=a²-2ab+b²

(4√3-7)²=(4√3)²-2×4√3×7+7²=16×3-56√3+49=48-56√3+49=97-56√3

tutaj trzeba po prostu pomnożyć liczby
(2+3√5)×(3-2√5)=2×3-2×2√5+3√5×3-3√5×2√5=6-4√5+9√5-6×5=6+5√5-30=5√5-24